Contribution Of Financial Inclusion In The Attainment Of Sustainable Development Goals - Mehirig, Adnane (جامعة الوادي - University of Eloued, 2021)
The study aims to clarify the contribution of financial inclusion to achieving sustainable development goals, by reviewing the literature and applied evidence of the benefits of financial inclusion for individuals in general, women and poor people in particular. Reviewing recent empirical evidence on how to use of financial products, such as payments services, savings accounts, loans and insurances, can contribute to achieving sustainable development goals. The result of this study highlights the potentials of financial inclusion that helps to achieve some of the 17 UN SDG. The direct contributions of financial inclusion to attain SDGs 1,2,3,4,5,6,7,8,9 and 10,16 in particular, It has also been noted that financial inclusion will accelerate enterprise development and job creation and thereby contributing immensely to economic growth and poverty alleviation.
مقال
Keywords: Financial inclusion, Financial exclusion, Sustainable Development Goals (SDGs)